Validation of the 'United Registries for Clinical Assessment and Research' [UR-CARE], a European Online Registry for Clinical Care and Research in Inflammatory Bowel Disease. (3rd February 2018) - Burisch, Johan; Gisbert, Javier P; Siegmund, Britta; Bettenworth, Dominik; Thomsen, Sandra Bohn; Cleynen, Isabelle; Cremer, Anneline; Ding, Nik John Sheng; Furfaro, Federica; Galanopoulos, Michail; Grunert, Philip Christian; Hanzel, Jurij; et al.
Abstract: Background: The 'United Registries for Clinical Assessment and Research' [UR-CARE] database is an initiative of the European Crohn's and Colitis Organisation [ECCO] to facilitate daily patient care and research studies in inflammatory bowel disease [IBD]. Herein, we sought to validate the database by using fictional case histories of patients with IBD that were to be entered by observers of varying experience in IBD. Methods: Nineteen observers entered five patient case histories into the database. After 6 weeks, all observers entered the same case histories again. For each case history, 20 key variables were selected to calculate the accuracy for each observer. We assumed that the database was such that ≥ 90% of the entered data would be correct. The overall proportion of correctly entered data was calculated using a beta-binomial regression model to account for inter-observer variation and compared to the expected level of validity. Re-test reliability was assessed using McNemar's test. Results: For all case histories, the overall proportion of correctly entered items and their confidence intervals included the target of 90% (Case 1: 92% [88–94%]; Case 2: 87% [83–91%]; Case 3: 93% [90–95%]; Case 4: 97% [94–99%]; Case 5: 91% [87–93%]). These numbers did not differ significantly from those found 6 weeks later [NcNemar's test p > 0.05]. Conclusion: The UR-CARE database appears to be feasible, valid and reliable as a tool and easy to use regardless of prior user experience and level of clinical IBD experience. UR-CARE has the potential to enhance future European collaborations regarding clinical research in IBD.